openSAP: Evaluating xMOOC Usage and Challenges for Scalable and Open Enterprise Education - Renz, Jan; Schwerer, Florian; Meinel, Christoph (International Journal of Advanced Corporate Learning (iJAC), 2016)
The openSAP University is a co-innovative initiative founded in 2013 by SAP SE in partnership with the Hasso-Plattner-Institute (HPI) located in Potsdam, Germany. With its new course offering, SAP responds to a rising demand for scalable knowledge transfer due to the digital transformation by making use of the Massive Open Online Courses (MOOC) format. This paper provides a brief introduction to the first Enterprise MOOC platform openSAP, including details about the learning environment and the underlying platform, different team roles and usage statistics. In addition, the topic of dropouts in enterprise MOOCs will be addressed and discussed. A standardized calculation model for enterprise MOOCs to measure completion and consumption rates is proposed. The paper closes with an outlook about the future work on enterprise MOOCs.